2010
DOI: 10.1007/s11682-010-9103-2
|View full text |Cite
|
Sign up to set email alerts
|

The neuroanatomic correlates of semantic memory deficits in patients with Gulf War illnesses: a pilot study

Abstract: We used functional magnetic resonance imaging (fMRI) to study semantic memory processing in 38 Gulf War veterans in 3 affected groups (Syndromes 1, 2, and 3) and normal-deployed controls. Subjects were given the Semantic Object Retrieval Test (SORT), which requires participants to decide whether two features combine and result in the retrieval of a specific object (e.g., "desert" and "humps" → "camel"). Differences between groups were calculated using a repeated measures analysis of variance (ANOVA). Then, reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
2
20
1
Order By: Relevance
“…MR studies conducted in 2008–2009 have also shown abnormalities of baseline rCBF and responses of rCBF to cholinergic challenge in hippocampus and in amygdala and caudate (Li et al, 2011, Liu et al, 2011) in ill Gulf War veterans from this same cohort. The abnormal brain responses to heat stimuli found in this study (in veterans with Syn1 and Syn2) and data from other recent neuroimaging studies (Calley et al, 2010, Li et al, 2011, Liu et al, 2011) underscore that GWI is not a single homogeneous illness and lend support to the validity of the classification of three primary syndrome groups from factor analysis of symptoms (Haley and Kurt, 1997, Iannacchione, et al, 2011). Furthermore, the war-related brain damage in these ill veterans from the Persian Gulf War appears distinct from more general effects of PTSD (Li et al, 2011) and of chronic pain symptomatology as in FM.…”
Section: Discussionsupporting
confidence: 74%
“…MR studies conducted in 2008–2009 have also shown abnormalities of baseline rCBF and responses of rCBF to cholinergic challenge in hippocampus and in amygdala and caudate (Li et al, 2011, Liu et al, 2011) in ill Gulf War veterans from this same cohort. The abnormal brain responses to heat stimuli found in this study (in veterans with Syn1 and Syn2) and data from other recent neuroimaging studies (Calley et al, 2010, Li et al, 2011, Liu et al, 2011) underscore that GWI is not a single homogeneous illness and lend support to the validity of the classification of three primary syndrome groups from factor analysis of symptoms (Haley and Kurt, 1997, Iannacchione, et al, 2011). Furthermore, the war-related brain damage in these ill veterans from the Persian Gulf War appears distinct from more general effects of PTSD (Li et al, 2011) and of chronic pain symptomatology as in FM.…”
Section: Discussionsupporting
confidence: 74%
“…Although previous studies (Mohamed et al, 2004;Calley et al, 2010) reported a significant negative association between fMRI signal changes and RT for other tasks, in the present study, it seems plausible that some difficulties in decision making of brightness preference consume both time and bran activity, leading to the demonstrated significant positive association. Nonetheless, it cannot be ruled out that brightness preference may also require preference decision via other brain regions potentially associated with preference such as the amygdala.…”
Section: Discussioncontrasting
confidence: 77%
“…In this same construction battalion, correlations of functional brain activity in the thalamus and caudate with semantic memory performance have been noted in a recent functional MR imaging study ( 31 ), and an evoked response potential investigation has shown that ill veterans have impaired response inhibition associated with reduced amplitude in the P3 evoked response ( 32 ).…”
Section: Discussionmentioning
confidence: 85%